Pengaruh Kepemimpinan Transformasional Dan Keterlibatan Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Perhubungan Kabupaten Buton Selatan - Masnia Masnia; Fitri Kumalasi; Andry Stepahnie Titing (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study aims to determine: (1) The effect of transformational leadership on employee performance at the Kab. South Buton. (2) The Effect of Work Involvement on Employee Performance at the Kab. South Buton. This study uses a quantitative method approach. Collecting data in this study using interviews, literature study, and distributing questionnaires. The population of this study were all employees at the South Buton District Transportation Service Office. While the sample of this study amounted to 68 people. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 3.0. Based on the research results it is known that Transformational Leadership has a positive and significant effect on performance. This is evidenced by the t- statistic value of 4.381 with a P- Value of 0,000. While the variable Work Involvement has a positive and significant effect on performance as shown by the t- statistic value of 4.369 with a P- Value of 0.000.